Intrauterine Adhesion Band Causing Fetal Leg Compression: A Case Report of a Rare Asherman Syndrome Complication in Pregnancy - Hangen Rodriguez, Sara Gabriela; Kupec, Tomáš; Freerksen-Kirschner, Nele Kristin; Wittenborn, Julia; Najjari, Laila; Stickeler, Elmar; Meyer-Wilmes, Philipp (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
Asherman syndrome (AS), characterized by intrauterine adhesions, can lead to various pregnancy complications. We report a case of a 31-year-old woman who was admitted at 29+2 weeks due to preterm premature rupture of membranes at our university hospital. The woman had a history of AS following emergency curettage. Ultrasonography revealed an adhesion band in the lower uterine segment, closely positioned to the fetus's leg. Antibiotic therapy and antenatal corticosteroids were administered to prevent infection and neonatal respiratory distress syndrome. Two weeks later, the woman developed labor contractions and pathological cardiotocography, leading to a secondary cesarean section. During surgery, the fetus was found to be in an incomplete breech position, with one leg trapped beneath the adhesion band. Delivery was achieved by releasing the other leg and cutting the adhesion band. The neonate was born with significant right leg edema, likely due to chronic intrauterine compressionby the adhesion band. Postoperatively, the neonate required intensive care. Regular orthopedic visits confirmed intact circulation, sensory, and motor function of the leg and the edema gradually resolved. This case highlights a rare pregnancy complication due to an intrauterine adhesion band and emphasizes the importance of accurate and early adhesion band detection such as the differential diagnostic exclusion of the more common amniotic band via ultrasound. It is a good example of multidisciplinary care provided by obstetricians, neonatologists and orthopedic surgeons in a perinatal care center.Asherman-Syndrom (AS) kann zu verschiedenen Schwangerschaftskomplikationen führen. Wir berichten über den seltenen Fall einer 31-jährigen, die in der 29.+2 Schwangerschaftswoche wegen eines vorzeitigen Blasensprungs eingeliefert wurde. In der Vorgeschichte war ein AS nach Notfallkürettage bekannt. Die Sonographie zeigte einen Adhäsionsstrang im unteren Uterinsegment mit engem Lagebezug zum Bein des Fötus. Eine Antibiotikatherapie und Lungenreifung (RDS-Prophylaxe) wurden eingeleitet. Zwei Wochen später erfolgte bei regelmäßiger Wehentätigkeit mit pathologischem CTG ein sekundärer Kaiserschnitt. Intraoperativ war das Bein des Fötus unterhalb des Adhäsionsstranges in unvollständiger Steißlage eingeklemmt. Durch Lösen des anderen Beins und Durchtrennen des Stranges gelang die Entbindung. Das Neugeborene hatte postpartal ein ausgeprägtes Ödem des rechten Beins, vermutlich durch chronische intrauterine Kompression des Adhäsionsstrangs. Postoperativ benötigte dasNeugeborene Intensivpflege. Regelmäßige orthopädische Visiten bestätigten eine intakte Durchblutung sowie sensorische und motorische Funktionen des Beins und das Ödem bildete sich im stationären Verlauf zurück. Dieser Fall zeigt eine seltene geburtshilfliche Komplikation durch einen intrauterinen Adhäsionsstrang und betont die Bedeutung der frühzeitigen, korrekten sonographischen Detektion sowie des differentialdiagnostischen Ausschlusses des häufigeren Amnionbandes. Es ist ein gutes Beispiel für die multidisziplinäre Betreuung durch Geburtshelfer, Neonatologen und Unfallchirurgen in einem Perinatalzentrum.
Keywords: Asherman syndrome; intrauterine adhesion band; fetal leg compression; pregnancy complication; multidisciplinary care